Sensitivity and Tolerance of Different Annual Crops to Different Levels of Banana Shade and Dry Season Weather - Blomme, Guy; Ntamwira, Jules; Kearsley, Elizabeth; Bahati, Liliane; Amini, Daniel; Safari, Nancy; Ocimati, Walter (Frontiers in Sustainable Food Systems, 2020)
Intercropping in small-holder banana-based production systems is a highly common practice in East and Central Africa with potential significant yield and environmental benefits. The reduced light availability under the banana canopy however highly constrains the success of the intercrop. Assessing the balance of optimal spacing densities of the banana plants and optimized intercrop selection based on their shade-tolerance is imperative. In this study, we investigate the resilience of a wide variety of food and feed crops to varying shade levels of open to dense banana fields through extensive field trials performed in South Kivu, DR Congo. Based on quantitative yield assessments of crops grown as monocrop and intercrop in diverse banana fields, we show that yam, sweet potato, ginger and forage grasses show good potential for use in (moderately) dense banana fields. Taro, soybeans, mucuna, chili, eggplant and Crotalaria performed well in sparsely spaced banana fields with moderate shading. Cassava and soybean showed limited tolerance to shade. Intercropping in banana systems is also generally confined to the rainy seasons due to the relatively low drought-tolerance of most annual crops. We also assess the drought-resilience of several crops and show that both chickpea and mucuna have great potential for extending farming production to the dry season. Overall, we show that careful selection and allocation of crops with varying shade-tolerance levels to various banana spacings and canopy densities and the use of drought-tolerant species during the dry season can highly increase whole farm productivity.